The beta-tubulin genes of Paramecium are interrupted by two 27 bp introns. - Dupuis, P (1992)
In the ciliate Paramecium tetraurelia, the analysis of the tubulin gene family has revealed the existence of four alpha and three beta genes. We show here that the coding sequence of the first beta-tubulin gene to be cloned and sequenced is interrupted by two short non-coding sequences of 27 bp each, which present at their extremities the pairs GT/AG, characteristic of eukaryotic pre-mRNA introns, and the internal pentanucleotide TTAAT, consensual in Tetrahymena introns. We demonstrate by PCR experiments that the three macronuclear beta-tubulin genes contain these sequences in similar positions, thereby ruling out the possibility that these sequences are ciliate IES present in the micronucleus and eliminated in the transcriptionally active macronucleus. S1 mapping analysis and mRNA sequencing show that the sequences are absent from the beta-tubulin transcripts. These sequences are the first introns described in protein encoding genes in P. tetraurelia and the shortest known introns altogether.